THE PROCEDURE FOR CALCULATING THE DURATION OF LABOR LEAVE - Turdikulov Makhtumquli Mirzaqulovich (Ecominds Press, 2025)
The article discusses the norms established by the legislation on the calculation of labor holidays in accordance with the labor legislation of the Republic of Uzbekistan. It also covers the social rights of the employee in labor relations.
Keywords: Vacation, period, Labor Code, working week, additional vacation, illegal actions, time.